The unexplored relationship between spontaneous osteoclastogenesis and platelets in osteoporosis - Salamanna, Francesca; Di Martino, Alberto; Contartese, Deyanira; Faldini, Cesare; Giavaresi, Gianluca; Fini, Milena (Frontiers in Medicine, 2025)
Spontaneous osteoclastogenesis, a phenomenon characterized by the unregulated differentiation and activation of osteoclasts in the absence of exogenous stimulatory factors, plays a central role in osteoporosis. While conventionally attributed to an imbalance between osteoclast and osteoblast activity, as well as to factors they release and/or produce, and to the involvement of T cells, emerging evidence suggests that platelets may contribute to this process beyond their established role in hemostasis. In this opinion, we propose that platelet activation and the subsequent release of cytokines, growth factors, and chemokines, including PDGF, IL1β, TGFβ, MIP-1α, TNFα, CXCL12 (SDF1), and CCL5 (RANTES), create a pro-inflammatory and osteoclastogenic microenvironment. These mediators may enhance RANKL production, recruit osteoclast precursors, and disrupt osteogenic signaling, indirectly fostering spontaneous osteoclastogenesis. Additionally, platelet interactions with endothelial cells, macrophages, and immune populations could further amplify inflammatory responses and sustain chronic bone resorption, contributing to the stimulation of spontaneous osteoclastogenesis. Although direct evidence linking platelets activation to spontaneous osteoclastogenesis is not yet available, existing literature supports the plausibility of this interplay. Exploring this underrecognized platelet-bone axis could provide new insights into osteoporosis pathophysiology and open avenues for novel diagnostic and therapeutic strategies. These hypotheses may be assessed in clinical practice to develop innovative approaches for the screening, diagnosis, monitoring and treatment of osteoporosis.